FAKTOR-FAKTOR YANG MEMPENGARUHI PENINGKATAN LOYALITAS PELANGGAN BLIBLI.COM - Diana Aqmala; Febrianur Ibnu Fitroh Sukono Putra; Rika Wijayani (Holistic Journal of Management Research, 2021)
The rapid development of technology in Indonesia which is accompanied by an increase of public intelligence to utilizing technology encourages the e-commerce entreprises to further increase the complexity of their business, so it will makes the competitors difficult to imitate and makes the customers become more loyal. The factors which can increase the customer loyalty including ease of use, quality of information, and trust. This strategic variables have significant effect on the existence of e-commerce enterprises in the industry, thus makes the companies need to prioritize these variables in decision making process. Therefore, this research aims to analyze the effect of ease of use, information quality, and trust on increasing the customer loyalty at blibli.com. The sampling method used was purposive sampling by drawing a sample size of 200 respondents. The analytical tool used is Structural Equation Modeling (SEM). The results of this research indicate that ease of use, information quality, and trust mediated by customer satisfaction significantly increase customer loyalty.